2010
DOI: 10.1016/j.fsi.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, and expression pattern of Atlantic halibut (Hippoglossus hippoglossus L.) CD4-2, Lck, and ZAP-70

Abstract: Havforskningsinstituttets institusjonelle arkiv Brage IMR - Institutional repository of the Institute of Marine Research b r a g e i m rDette er forfatters siste versjon av den fagfellevurderte artikkelen, vanligvis omtalt som postprint. I Brage IMR er denne artikkelen ikke publisert med forlagets layout fordi forlaget ikke tillater dette. Du finner lenke til forlagets versjon i Brage-posten. Det anbefales at referanser til artikkelen hentes fra forlagets side. Ved lenking til artikkelen skal det lenkes til po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…This result is similar to earlier findings from other fish species [20, 21, 62, 63]. In addition, previous work in our lab using whole mount in situ hybridization (WISH) with a CD4-1 antisense RNA probe demonstrated that the zfCD4-1 was also expressed within the developing thymus in zebrafish embryos 4 days post fertilization [64].…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to earlier findings from other fish species [20, 21, 62, 63]. In addition, previous work in our lab using whole mount in situ hybridization (WISH) with a CD4-1 antisense RNA probe demonstrated that the zfCD4-1 was also expressed within the developing thymus in zebrafish embryos 4 days post fertilization [64].…”
Section: Discussionsupporting
confidence: 91%
“…In healthy tilapia, the highest expression level of ZAP-70 was detected in thymus, followed by spleen and head kidney, which is similar to what is seen for Atlantic halibut ZAP-70 (Overgard et al 2010). This pattern of expression is consistent with sites of lymphopoiesis in teleost.…”
Section: Discussionsupporting
confidence: 76%
“…In mammals, ZAP-70 is found to interact through its tandem SH2 domains, with phosphorylated ITAMs within the CD3 chains. These two features are conserved in all ZAP-70 (Christie et al 2010;Nunez Ortiz et al 2014;Overgard et al 2010) and CD3 (Laing and Hansen 2011) sequence characterized in teleosts, respectively, implying the interaction between ZAP-70 and CD3 in mammals is conserved in teleosts. The high conservation of the tandem SH2 domains of On-ZAP-70 agrees with this.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations